A presença sonora no constructo cinematográfico: análise dos sons acusmáticos no filme A Mulher sem piano - Gehlen, Luiz Henrique (Universidade do Vale do Rio dos Sinos, 2017)
The present thesis is inserted in the Media and Audiovisual Processes research line, and its general objective is to discuss the sonorous presence, by using of acousmatic sounds in cinema. Our argument is built in consonance with the need to problematize sound as an expressive element in the sensory experience of the cinematographic images universe, taking in consideration the aesthetic contribution that technical sonorities offer to modern cinema. For this, the theoretical foundation is built mainly on the concepts proposed by Gilles Deleuze, Walter Benjamin, Hans Ulrich Gumbrecht, Didi-Huberman and Michel Chion. In order to achieve our objectives, it is used a qualitative methodology built with emphasis on the methods: Intuitive, scanning, cartography and the disconnection inspired by Michel Chion, for which we try to authenticate the updates of the sonorous presence - the dimension of listening and the sonorous presence as a updating potency of the bodies - in the movie The Woman Without a Piano (2009), directed by Javier Rebollo, that represents the emergent aesthetics of the "new spanish cinema".
Keywords: Presença sonora; Acusmática; Aurático; Cinema espanhol; Cinema moderno; Sonorous presence; Acousmatic; Auratic; Spanish cinema; Modern cinema; ACCNPQ::Ciências Sociais Aplicadas::Comunicação